Totem Beliefs in Karachay-Balkar Folklore and Literature - Bolatova, Asiat Dautovna; Uzdenova, Fatima Taulanovna; Kerimova, Rauzat Abdullakhovna (Journal of History Culture and Art Research, 2019)
The paper considers a set of the totemic beliefs as archaic views spread among ancient Turkic peoples, in particular the Karachays and Balkars. We have studied ways and forms of pagan manifestation in the ethnic traditions, cultural consciousness and Balkar literature. In the course of the study, we have touched upon issues concerning the mythoepic tradition and symbolic generalizations. We have used folklore to trace the continuity of artistic thought-tide in understanding and interpreting symbols (tree, stone, etc.). We have also identified mythologems (mother goddess) through zoomorphic images (deer, she-wolf). One can still find mythology and folklore samples in other nations’ literature presenting ancient legends of totem ancestors. They synthesized the rudimentary forms of religion. The characters of the stories were endowed with both zoomorphic and anthropomorphic traits. In addition to the traditional animal cult worshiped by the Turkic peoples there were the cult of ancestors, obeisance to the spirits of the dead. The ritual to distribute the meat portions of a sacrificial animal between members of the same clan also considered as a symbolic act.